The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1365-2516.2010.02200.x
|View full text |Cite
|
Sign up to set email alerts
|

Balance dysfunction in adults with haemophilia

Abstract: The main focus of lower limb physical performance assessment in people with haemophilia (PWH) has usually been on function, muscle strength and joint flexibility. The impact of haemophilic arthropathy on balance and falls risk is relatively under-explored. The aim of this study was to evaluate balance and related performance in PWH compared with age and gender matched healthy controls. It involved a comprehensive suite of clinical and laboratory measures of static and dynamic balance, mobility, strength, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
104
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(121 citation statements)
references
References 23 publications
11
104
4
2
Order By: Relevance
“…Actualmente podemos decir que, en general, la condición física del paciente hemofílico adulto es baja, ya que hay estudios que muestran valores inferiores de resistencia aeróbica 49 , fuerza 37,50,51 , propiocepción y equilibrio 50,52,53 , respecto a los encontrados en sus pares sanos.…”
Section: La Condición Física Del Paciente Hemofílicounclassified
“…Actualmente podemos decir que, en general, la condición física del paciente hemofílico adulto es baja, ya que hay estudios que muestran valores inferiores de resistencia aeróbica 49 , fuerza 37,50,51 , propiocepción y equilibrio 50,52,53 , respecto a los encontrados en sus pares sanos.…”
Section: La Condición Física Del Paciente Hemofílicounclassified
“…Gallach et al [21] compared standing balance in a group of 50 adult PWH and 25 age-matched healthy non-haemophilic men and observed greater amplitude and velocity of postural sway in men with haemophilia during standing. In a study of twenty PWH aged 22-58 years, Fearn et al [22] reported that half of haemophilic men had experienced a fall within the previous 12 months. The underlying cause of the alterations in balance and greater frequency and risk of falling together with how best to identify those at risk of falling are not clear from the studies.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic characters of hemophilic patients include musculoskeletal pain, muscle imbalance [7], reduced joint range of motion [8], and articular instability [9]. Balance performance is complex and multidimensional, involving not only the ability to maintain a static stance, but also the ability to maintain equilibrium under a range of dynamic conditions [10]. Few of studies have addressed the impact of musculoskeletal disorders in hemophiliacs on balance impairment or fall.…”
mentioning
confidence: 99%
“…Results showed that patients with hemophilia displayed a worse balance and proprioception compared with healthy normal subjects [10][11][12][13].Authors hypothesized that because proprioception information is transmitted from receptors found in all tissues of the synovial joint, repeated joint bleeding into the target joint could be a contributory cause of impaired proprioception in patients with hemophilia. As the muscular function comprises not only the static control of the joint and the dynamic control of movement, but also the proprioceptive input to the central nervous system (CNS) .So further possible mechanism induced proprioception deficit in hemophilic patients may be related to the intramuscular bleeding and lower muscle strength [14,15].…”
mentioning
confidence: 99%